Pengembangan Media Flipbook dalam Meningkatkan Pemahaman Materi Keragaman Suku Bangsa Indonesia Mata Pelajaran PPKN untuk Siswa Kelas IV MI Ma’Arif 18 - Lutfiatun Nasiroh; Masrurotul Mahmudah; Lutfi Fadilah (FONDATIA, 2026)
This study was motivated by students’ low understanding of the material on the ethnic diversity of Indonesia due to learning that remains conventional and the minimal use of engaging media. This study aims to develop flipbook-based learning media, analyze the feasibility of the developed media, and examine the improvement in the understanding of fourth-grade students at MI Ma’arif 18 Trimurjo. This study employed the Research and Development method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) and involved 21 students selected through the saturated sampling technique. Data were collected through interviews, questionnaires, tests (pretest and posttest), and documentation, and were then analyzed descriptively and quantitatively. The results showed that the developed flipbook media obtained a very valid category from the media expert with an average score of 4.71 (94.28%) and from the material expert with an average score of 4.83 (96.67%). The use of flipbook media was also proven to increase students’ activeness, interest, and understanding, as indicated by improved abilities in the cognitive indicators of Bloom’s Taxonomy, namely remembering, understanding, applying, analyzing, evaluating, and creating. These findings indicate that visual- and interactive-based learning media are effective in improving the quality of the learning process and learning outcomes. Thus, flipbook media are feasible and effective for improving students’ understanding of the material on the ethnic diversity of Indonesia and provide theoretical and practical contributions to the development of more engaging, interactive, and meaningful learning.